(untitled) (Jurnal Destinasi Pariwisata, 2025)
This study aims to determine the impact of tourism development on the social and cultural life of the community in Cemagi Tourism Village, Mengwi District, Badung Regency. This study uses a qualitative descriptive comparative study approach through observation, structured interviews, literature study, and documentation techniques. The results of the study indicate that before the development of tourism, the social life of the Cemagi community was dominated by an agrarian and maritime system with a cooperative pattern (seka manyi), while cultural aspects such as art and language were primarily used in sacred and traditional ceremonial contexts. Following the development of tourism, particularly after 2021–2022, Cemagi Tourism Village is currently in the development phase, with significant increases in the number of tourist visits, attractions, accessibility, amenities, and additional services. Additionally, tourism development has brought positive impacts such as increased community participation in tourism management, the preservation of local arts as tourist attractions, and the creation of job opportunities. However, there are also negative impacts such as land use conversion, cultural commodification, and social conflicts due to the lack of appropriate regulations. Therefore, while tourism brings various benefits to the community, strategies for cultural preservation and spatial planning are still needed to ensure the sustainability of the tourism village